2018
DOI: 10.1016/s0168-8278(18)30549-x
|View full text |Cite
|
Sign up to set email alerts
|

Khat chewing increases the risk for developing chronic liver disease: A hospital-based case-control study

Abstract: The chewing of the leaves of Catha edulis (khat) has been implicated in the development of liver disease, but no controlled observations have been undertaken. The objective of the present study was to determine whether khat chewing is associated with development of chronic liver disease (CLD). A case-control study was conducted at two public hospitals in Harar, Ethiopia, between April 2015 and April 2016. A consecutive sample of 150 adult hospital attendees with CLD were included as cases, and 300 adult hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…15 Another study found a 1.3% HCV prevalence in these patients. 51 Hepatitis C virus infection in chronic hepatitis patients is a source of healthcare-associated HCV infection between patients, healthcare workers, and other susceptible individuals. Diagnosis and treatment of HCV infection in this population is vital to improve the quality of life and disease progression of the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…15 Another study found a 1.3% HCV prevalence in these patients. 51 Hepatitis C virus infection in chronic hepatitis patients is a source of healthcare-associated HCV infection between patients, healthcare workers, and other susceptible individuals. Diagnosis and treatment of HCV infection in this population is vital to improve the quality of life and disease progression of the patients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Chewing is associated with the development of chronic liver disease (CLD). The research was carried out on 150 patients in 2015 and 2016 and another trial of 150 adult hospital patients with CLD and 300 adult hospital participants without clinical or laboratory evidence of CLD were included as controls [104]. Khat use was quantified in "khat years"; 1 year khat was defined as the daily use of 200 g fresh khat for 1 year.…”
Section: Risk Assessment Of Potential Harmfulness Pesticidementioning
confidence: 99%
“…It is estimated that tobacco-related diseases are now the cause of every tenth death in the world. No other single, equally deadly agent is known, a virus, a bacterium or a genetic defect that would cause so many illnesses and deaths [104,105]. Nicotine activity in tobacco products is stimulant and then infectious on connections in the nerve ganglia, and especially on the Deadly dose from 50 mg, which corresponds to 2-3 cigarettes taken orally.…”
Section: Risk Assessment Of Potential Harmfulness Pesticidementioning
confidence: 99%
“…Chewing khat is a social and cultural habit practiced by Yemeni and East African peoples [2]. The tender, reddishgreen leaves and the young shoots (Figure 1) are chewed for several hours daily to get the desired effects [3]. Generally, people chew khat for its stimulant effects on nervous system and reducing fatigue and restore mental and physical activity [4].…”
Section: Introductionmentioning
confidence: 99%